2004
DOI: 10.1242/jcs.00909
|View full text |Cite
|
Sign up to set email alerts
|

The role of annexin 2 in osteoblastic mineralization

Abstract: While the basic cellular contributions to bone differentiation and mineralization are widely accepted, the regulation of these processes at the intracellular level remains inadequately understood. Our laboratory recently identified annexin 2 as a protein involved in osteoblastic mineralization. Annexin 2 was overexpressed twofold in SaOSLM2 osteoblastic cells as a fusion protein with green fluorescent protein. The overexpression of annexin 2 led to an increase in alkaline phosphatase activity as well as an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 52 publications
4
78
0
1
Order By: Relevance
“…A scaffolding function of AnxA2 that can cluster PI(4,5)P 2 and other interacting lipids into larger domains is likely to be of relevance in several membrane related signaling and transport events. These include the formation of actin assembly sites at the plasma membrane (14,47), the organization of lipid domains (rafts) in sarcolemmal differentiation and during osteoblastic mineralization (56,57), and the formation of rafts required for efficient exocytosis of dense core granules in neuroendocrine cells (16). Thus, the novel properties reported here for AnxA2 and its derivatives using artificial membrane systems could represent the molecular basis of AnxA2 activities observed in cells.…”
Section: Discussionmentioning
confidence: 89%
“…A scaffolding function of AnxA2 that can cluster PI(4,5)P 2 and other interacting lipids into larger domains is likely to be of relevance in several membrane related signaling and transport events. These include the formation of actin assembly sites at the plasma membrane (14,47), the organization of lipid domains (rafts) in sarcolemmal differentiation and during osteoblastic mineralization (56,57), and the formation of rafts required for efficient exocytosis of dense core granules in neuroendocrine cells (16). Thus, the novel properties reported here for AnxA2 and its derivatives using artificial membrane systems could represent the molecular basis of AnxA2 activities observed in cells.…”
Section: Discussionmentioning
confidence: 89%
“…If either fetuin-A is not carrying calcium, or annexins are blocked, then neither calcium nor fetuin-A enters the cells. This is plausible in that annexins are known to facilitate membrane conformational changes and the formation of lipid rafts that facilitate endocytosis in osteoblasts (7). Several studies have demonstrated that annexins are present on endosomal compartments and involved in endocytosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…(46)(47)(48)(49)(50) Furthermore, at least in hypertrophic chondrocytes, the release of mineralization-competent matrix vesicles coincides with the translocation of PS from the inner to the outer leaflet of the plasma membrane. (47) This process, denoted as phospholipid scrambling, is regulated by members of the phospholipid scramblase protein family.…”
Section: Regulation Of Ps Translocation In Osteoblasts By Ano6mentioning
confidence: 99%